The First Challenges of the Russian Princes to the Mongol Rulers: Years 1242–1243 - Gorsky A.A. (Золотоордынское обозрение)
Abstract: Research objectives: The article aims to reveal the time, circumstances and consequences of the first demands of Mongol conquerors to the main Russian princes to visit the residence of Batu. Research materials: The texts of Old Russian chronicles – Hypatian, Laurentian, First Novgorod and others, Vita of Mikhail Chernigovskiy, “History of the Mongols” by John of Plano Carpini. Results and novelty of the research: It is established that at the end of 1242 – the beginning of 1243 the demands to visit the residence of Batu (who just returned from the campaign in Central Europe) were received by all three of the strongest Russian Princes – Yaroslav Vsevolodich, Mikhail Vsevolodich and Daniil Romanovich. The decision to leave the Russian princes in their possessions at that moment was not accepted yet, and the possibility of the earlier employed Mongol regime of direct control remained. Mikhail and Daniil shied away from the visit, while Yaroslav came to Batu and received an all-Russian ‘seniority’. These events predetermined the establishment of a model of rule in Rus’ through local rulers.